Assessment of right ventricular function following left ventricular assist device (LVAD) implantation—The role of speckle‐tracking echocardiography: A meta‐analysis. Issue 12 (20th October 2020) - Barssoum, Kirolos; Altibi, Ahmed M.; Rai, Devesh; Kharsa, Adnan; Kumar, Ashish; Chowdhury, Medhat; Elkaryoni, Ahmed; Abuzaid, Ahmed Sami; Baibhav, Bipul; Parikh, Vishal; Masri, Ahmad; Amsallem, Myriam; et al.
Abstract: Background: Right ventricular failure (RVF) following left ventricular assist device (LVAD) implantation is associated with worse outcomes. Prediction of RVF is difficult with routine transthoracic echocardiography (TTE), while speckle‐tracking echocardiography (STE) showed promising results. We performed systematic review and meta‐analysis of published literature. Methods: We queried multiple databases to compile articles reporting preoperative or intraoperative right ventricle global longitudinal strain (RVGLS) or right ventricle free wall strain (RVFWS) in LVAD recipients. The standard mean difference (SMD) in RVGLS and RVFWS in patients with and without RVF postoperatively was pooled using random‐effects model. Results: Seventeen studies were included. Patients with RVF had significantly lower RVGLS and RVFWS as compared to non‐RVF patients; SMD: 2.79 (95% CI: −4.07 to −1.50; P : <.001) and −3.05 (95% CI: −4.11 to −1.99; P : <.001), respectively. The pooled odds ratio (OR) for RVF per percentage increase of RVGLS and RVFWS were 1.10 (95 CI: 0.98–1.25) and 1.63 (95% CI 1.07–2.47), respectively. In a subgroup analysis, TTE‐derived GLS and FWS were significantly lower in RVF patients as compared to non‐RVF patients; SMD of −3.97 (95% CI: −5.40 to −2.54; P : <.001) and −3.05 (95% CI: −4.11 to −1.99; P : <.001), respectively. There was no significant difference between RVF and non‐RVF groups in TEE‐derived RVGLS and RVFWS. Conclusion: RVGLS and RVFWS were lower in patients who developed RVF as compared to non‐RVF patients. In a subgroup analysis, TTE‐derived RVGLS and RVFWS were reduced in RVF patients as compared to non‐RVF patients. This difference was not reported with TEE.